Administration of fiscal regimes for petroleum exploration and development (United nations, 1995)
The book provides technical assistance related to formulating or reviewing national petroleum policies, laws and regulations, including taxation in the petroleum sector; assessing the merits of alternative forms of contractual arrangements taking into account national objectives and resources; formulating or reviewing bidding arrangements and procedures; drafting or reviewing model contracts and undertaking related economic and computer analyses; evaluating the economic, financial, legal and operational aspects of specific proposed contractual arrangements with TNCs (Transnational Corporations), including the formulation of negotiating positions and strategies; and formulating or reviewing legislative, institutional and other arrangements related to the etablishment, functions and operations of national petroleum companies